Heterotetranuclear Complexes of Reduced and Non‐reduced Bridging 1, 2, 4, 5‐Tetrazine Ligands with 1, 1′‐Bis(diphenylphosphanyl)‐ferrocene‐copper(I)12. Issue 2 (30th January 2015) - Bach, Monika; Roy, Sayak; Sarkar, Biprajit; Bubrin, Martina; Niemeyer, Mark; Fiedler, Jan; Duboc, Carole; Kaim, Wolfgang
Abstract The complexes {(μ‐bptz)[Cu(dppf)]2}(BF4)2 [(1)(BF4)2] [bptz = 3, 6‐bis(2‐pyridyl)‐1, 2, 4, 5‐tetrazine, dppf = 1, 1′‐bis(diphenylphosphanyl)ferrocene] and {(μ‐bpztz)[Cu(dppf)]2}(PF6)2 [(2)(PF6)2] [bpztz = 3, 6‐bis(2‐pyrazinyl)‐1, 2, 4, 5‐tetrazine] contain two redox‐active heterodinuclear FeIICuI moieties, bridged by a redox‐active ligand. A crystal structure determination of (1)(BF4)2·2CH2Cl2 confirms the non‐reduced aromatic nature of the bridge, in contrast to previous results on dicopper(I) complexes of bptz. Facile one‐electron reduction produces the radical complexes {(μ‐bptz)[Cu(dppf)]2}+ (1+) and {(μ‐bpztz)[Cu(dppf)]2}+ (2+), which could be isolated [as (1)(BF4)] and studied by variable frequency EPR to provide hyperfine (9.5 GHz) and g anisotropy information (285 GHz). Cyclic voltammetry and UV/Vis/NIR spectroelectrochemistry indicate a reversible two‐electron oxidation of the well separated (ca. 13.4 Å) ferrocene termini.